PRODUCTIVE CHARACTERISTICS OF A NEW VARIETY OF PURPLE POTATO (Solanum tuberosum cv. Bergerac) (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
Potato, as one of the most important crops in Bosnia and Herzegovina, covers an area of 35,000 ha with average yield of up to 12 t ha-1. New potato variety - Bergerac, with purple flash and skin color, has been used for comparison with traditionally used Desire variety. Research was carried out during 2021. Phenolics, as secondary metabolites, have great physiological impact, due to their antioxidative activity. Two ways of planting were used: with and without (control variant) microbiological fertilizer Slavol application. In both varieties, Slavol affected yield, height, and the number and size of tubers per plant.The average yield in the control variant (without the application of microbiological fertilizer) for the variety Dezire was 31.2 t ha-1 and 33.1 t ha-1 for the variety Bergerac.With Slavol, Desire variety achieved an average yield of 48.4 t ha-1, while Bergerac produced a yield of 37.1 t ha-1. The average number of tubers per plant was higher in Bergerac variety, while Desire had larger tubers (average diameter ≥40 mm). Study indicates that potatoes with purple flesh have a higher antioxidant activity. The antioxidant activity for the Bergerac variety was 53.7% higher then Desire with 267.23 mg GAE/kg FW, while Desire variety had average amount of 123. 68 mg GAE/kg FW.